2013
DOI: 10.1021/ja403757p
|View full text |Cite
|
Sign up to set email alerts
|

“Flex-Activated” Mechanophores: Using Polymer Mechanochemistry To Direct Bond Bending Activation

Abstract: We describe studies in mechanochemical transduction that probe the activation of bonds orthogonal to an elongated polymer main chain. Compression of mechanophore-cross-linked materials resulted in the release of small molecules via cleavage of covalent bonds that were not integral components of the elongated polymer segments. The reactivity is proposed to arise from the distribution of force through the cross-linking units of the polymer network and subsequent bond bending motions that are consistent with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
251
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(255 citation statements)
references
References 41 publications
2
251
0
2
Order By: Relevance
“…Those include explicit incorporation of the force term into a PES 21,[106][107][108] (as in Eq. (8)), using constraints to simulate stretching, 1,[109][110][111] numerical integration of Eqs. (3) and (4), 37,46,68,112 and approximations based on Eq.…”
Section: A Which Bond Breaks First?mentioning
confidence: 99%
“…Those include explicit incorporation of the force term into a PES 21,[106][107][108] (as in Eq. (8)), using constraints to simulate stretching, 1,[109][110][111] numerical integration of Eqs. (3) and (4), 37,46,68,112 and approximations based on Eq.…”
Section: A Which Bond Breaks First?mentioning
confidence: 99%
“…Control polymer in which the mechanophore was not covalently incorporated into the PMA matrix showed 6% conversion under the same conditions. Although a significantly high thermal background reaction observed with control polymer might limit its practical applications, this work represented an important step towards the realisation of autonomous self-healing materials, as the mechanogenerated acid could be used to catalyse cross-linking reactions in situ, thereby allowing the material to respond actively and constructively to mechanical force Reports have also emerged from the Boydston group describing the flex, or bondbending, activation of an oxanorbornadiene, a Diels-Alder adduct of furan and dimethyl acetylenedicarboxylate [58]. They incorporated the mechanophore into poly(methyl acrylate) (PMA) matrix and showed that the furan derivative could be released under stress applied to the bulk polymer (Fig.…”
Section: Mechanical Release Of Small Molecules In Polymer Matricesmentioning
confidence: 99%
“…As a result, the focus of studying mechanochemical degradation of polymers has shifted from optimization of processing properties to understand mechanochemical events at molecular level and to the development of functional mechano-responsive materials. The last decade has witnessed tremendous progress on the creation of mechano-responsive polymers [12][13][14][15][16][17][18][19][20]. Mechanical force has been used, for instance, to activate ring-opening [13,17,21] and cycloreversion reactions [14,15,22], to trigger latent polymeric catalysts [12,[23][24][25], to guide "flex activation" [16,26], to induce cross-linking reactions [24,27,28], to assemble or disassemble supramolecular polymers in a controlled manner [29][30][31][32][33][34], and so on.…”
Section: Introductionmentioning
confidence: 99%